Occupy Wall Street:: En bevægelse og dens intellekt(uelle) - Risager, Bjarke Skærlund (Slagmark - Tidsskrift for idéhistorie, 2018)
This article traces the various forms and roles of intellectuals and intellectualism in the Occupy Wall Street protest camp in Zuccotti Park in New York in 2011 while simultaneously serving as an introduction to the movement. It shows how the movement was formed by a range of intellectual ideas, both in terms of the political questions it posed and the tactics it employed. It also shows how Occupy affected the intellectual and political climate insofar as it became a phenomenon that everyone with an interest in public debate (and space!) had to take a stand on. The article argues that Occupy, with its experiment in alternative social and democratic structures, was an exercise in a form of organic and collective intelligence that attempted to guide American society in a more democratic and equal direction. By way of conclusion, the article discusses the aftermath of the protest camp and the effects of the movement.